Unlocking rapid electrocoagulation: performance of 3D porous aluminum electrodes for industrial textile wastewater treatment - Sgarbi, Ricardo; Ruotolo, Luis Augusto Martins (Universidade Federal de São Carlos, 2025)
In this work, a novel designed electrocoagulation (EC) reactor utilizing three-dimensional (3D) aluminum electrodes was investigated for industrial textile wastewater treatment. Statistical analysis revealed that operational parameters (current density, coagulation time, and flow rate) had a greater influence on process performance than wastewater properties (pH and conductivity), avoiding the need for chemical inputs. Optimal performance was achieved with shortest coagulation time, promoted by dual features: (i) a balanced combination of flotation and sedimentation for pollutant removal, and (ii) sufficient aluminum coagulant release and mixing turbulence promoted by the operational conditions. Thus, the operation achieved high removal efficiencies, 90 % for turbidity, 89 % for total organic carbon (TOC), and 69 % for color, within just 4 min, coupled with a low energy demand of ca. 1.1 kWh m−3. Furthermore, in-situ electrochemical potential profiling across the 3D Al electrode thickness confirmed the existence of a region between the cathode and anode that enhances collisions between released aluminum coagulant and pollutants, thus promoting floc formation and posterior segregation via sedimentation and flotation.
Keywords: Aluminum electrocoagulation; Electrocoagulation reactor; Textile effluent; Energy saving; Electrochemical potential profiling; 6. Água Potável e Saneamento